Audit on gynaecological surgeries in Ramaiah medical college and hospital in year 2025 - Reshme, Niveditha; Nagaraj, Punitha; G. S., Jyothi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Surgical audit is a peer-reviewed process to assess surgical quality and improve patient outcomes. In gynaecology, common surgeries include hysterectomy, dilatation and curettage, prolapse repair, laparoscopy, and myomectomy. This study aimed to evaluate the effectiveness, efficiency, and outcomes of gynaecological surgeries performed at Ramaiah Medical College and Hospital, Bengaluru, from January to March 2025, and to identify areas for improvement in surgical practice. Methods: This retrospective observational study included all patients who underwent gynaecological surgeries during the study period at Ramaiah Memorial Hospital. Data on demographics, indications, type of surgery, complications, anaesthesia, and hospital stay were collected and analysed using SPSS version 26.0. Results: A total of 52 gynaecological surgeries were conducted. The majority of patients were aged 50-55 years. Abnormal uterine bleeding (38%) was the most common indication. Hysterectomy was the predominant surgery (46%), performed mainly via the vaginal route (50%). Endoscopic procedures constituted 50% of surgeries, including hysteroscopies (32%) and laparoscopies (17%). Spinal anaesthesia was used in 62% of cases. The main complication was intraoperative blood loss requiring transfusion. The mean hospital stay was longest for abdominal hysterectomies (3-5 days). Conclusions: Most surgeries adhered to ACOG and RCOG recommendations, prioritising minimally invasive approaches. Vaginal and laparoscopic hysterectomies were preferred where feasible, reflecting evidence-based and patient-centred surgical practice.